Academic English at tertiary level: What, why and how - Nga, Nguyen Thi Hong (VNU Journal of Foreign Studies, 2009)
Abstract. Academic writing is arguably the most important language skill to tertiary students, especially to English-major ones, whose grades are largely determined by their performance in written assignments, academic reports, term examinations and graduation theses. However, reality has proved the difficulties of Vietnamese learners in applying the right level of formality, lexical dense, and objectivity. The article, with the hope to help the tertiary English- major students improve their skill of writing academic English, first deals with an overview on academic English and the necessity of equipping them with knowledge of academic English. It will also go on to put forward some strategies for effective writing academic English.